Surgical treatment of earlobe keloid with CO2 laser radiation: Case report and clinical standpoints - Cantarelli Morosolli, Aline Rose; Moura Cardoso, Gerusa de Oliveira [UNESP]; Murilo-Santos, Lucio [UNESP]; Niccoli-Filho, Walter [UNESP] (Informa Healthcare, 2008)
Keloids are considered to be benign hyperproliferative growths of dense fibrous tissue and overabundant deposition of disorganized, thick, hyalinized collagen that result from an abnormal tissue response to cutaneous injury. Keloids do not have a specific cause, although genetic predisposition is heavily implicated. We present a case report of a patient with an earlobe keloid that was treated with carbon dioxide laser radiation (CO2) with an 0.8-mm focus, 7 W, a power density of 2.5 W/cm(2), in a continuous mode. The patient was seen for follow-up 6 months later. An intact hole for placement of an earring was observed with a very good esthetic and functional result.
Keywords: Carbon dioxide laser radiation; hypertrophic scars; keloids; wound healing